Signalment, clinical characteristics, and echocardiographic findings in dogs affected by secondary atrial fibrillation with and without concomitant frequent and complex ventricular arrhythmias - Romito, Giovanni; Mazzoldi, Chiara; Riccio, Chiara; Fogli, Marcello; Paradies, Paola; Recchia, Alessandra; Pelle, Nazzareno Giuseppe; Testa, Fabio; Valente, Carlotta; Poser, Helen; Arcuri, Giulia; Contiero, Barbara; et al. (Frontiers in Veterinary Science, 2026)
IntroductionAssessment of dogs with atrial fibrillation (AF) and ventricular arrhythmias (VAs), two arrhythmias that can coexist, is traditionally based on 24-h Holter monitoring. However, this test may not always be feasible. The aim of this study was to determine whether alternative methods exist to distinguish dogs affected by secondary AF with frequent and complex VAs from those without.MethodsIn this multicenter retrospective study, electronic databases from five centers were searched for dogs with a diagnosis of secondary AF. For inclusion, complete clinical, echocardiographic and 24-h Holter data had to be available for each dog. Signalment, clinical, and echocardiographic variables of left cardiac dimension and function were compared between dogs with secondary AF exhibiting frequent ventricular premature complexes (VPCs; ≥100/Holter) or severe VAs (Lown-Wolf grade ≥4) and those without.ResultsFifty-nine dogs, including 35/59 (59.3%) dogs with myxomatous mitral valve disease, 17/59 (28.8%) dogs with dilated cardiomyopathy, and 7/59 (11.9%) dogs with congenital heart disease, were evaluated. Compensated and decompensated cardiac disease was diagnosed in 10/59 (16.9%) and 49/59 (83.1%) dogs, respectively. Holter monitoring detected VAs associated with AF in 58/59 (98.3%) dogs. Among dogs with VPCs, the median number of VPCs was 265 (1–1,759) and 32/59 (54.2%) dogs had ≥100 VPCs/Holter. Regarding VA complexity, 34/59 (57.6%) dogs exhibited a Lown-Wolf grade ≥4. Statistical analyses revealed that none of the 17 analyzed variables reached significance in differentiating dogs with and without frequent VPCs, as well as dogs with and without complex VAs.DiscussionIn dogs with secondary AF, VAs are usually present and are frequently of clinical relevance according to their Lown-Wolf grade. However, signalment, clinical presentation, and conventional echocardiographic data do not reliably distinguish dogs with frequent VPCs or complex VAs from those without, reinforcing the indispensable role of 24-h Holter monitoring for the accurate assessment of these subjects.